Sistem Informasi Manajemen Toko Buku Bibliophile’s Spot Berbasis Online - Fatihah, Amelia Alfie; Primadani, Ardi; ., Jessyca; Iman, Moh Nurul (Jurnal Sains dan Teknologi (JSIT), 2024)
With the growing market demand, the bookstore faces challenges in inventory management, transaction recording, and customer data management, which are often done manually, resulting in inefficiency and a high risk of errors. The main goal of this research is to design and implement a system that can automate these processes, making it easier for store management to manage stock, record transactions in real-time, and provide relevant information for decision-making. This research uses the Research and Development (R&D) method with an Agile approach in system development, allowing for gradual updates and responsiveness to user feedback. The use of this management information system not only reduces recording errors and accelerates the transaction process but also provides more flexible access through web and mobile-based applications. With the integrated system, transaction and inventory data can be accessed and updated in real-time, supporting management in conducting sales analysis and identifying product trends that customers are interested in.